THE ROLE OF PEDAGOGICS AND PSYCHOLOGY IN IMPROVING THE QUALITY AND EFFICIENCY OF EDUCATION AND THE FORMATION OF HUMAN VALUES AND PERFECT GENERATION - Meiliyeva Zebiniso (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article provides information about the role of pedagogy and psychology in improving the quality and effectiveness of education and the formation of a mature generation.